تعليمية الأنشطة البدنية والرياضية - تمساوت ، جيلالي (Mohamed Boudiaf University of M'Sila, 2025)
الملخص : بالعربية : مطبوعة تعليمية الأنشطة البدنية والرياضية موجهة لطلبة السنة الثانية ليسانس قسم النشاط البدني الرياضي المكيف يهدف التعرف على القواعد الأساسية للتخصص ومجالات استخدامه في الميدان الرياضي وكذلك القواعد الأساسية والمعارف النظرية والتطبيقية المرتبطة بالتخصص لرفع من مستوى المعرفي والتقني والخططي للطالب قصد رسم مستقبله. وهذا من أجل تلقين المعارف أو المعلومات والتي ينصح استعمالها لنجاح عملية التدريس. Searchlight in English An educational publication on physical and sports activities directed at second-year undergraduate students in the Adapted Physical Activity and Sports Department. It aims to introduce the basic principles of the specialty and its areas of application in the sports field, as well as the basic rules and theoretical and applied knowledge related to the specialty. This aims to raise the student's cognitive, technical, and planning level to shape their future. This is intended to impart knowledge and information, the use of which is recommended for the success of the teaching process.
Keywords: تعليمية; مكونات العملية التعليمية; التقويم